1990
DOI: 10.1055/s-2007-993618
|View full text |Cite
|
Sign up to set email alerts
|

Zur Arthrosegefährdung des oberen Sprunggelenkes bei Langstreckenläufern: Kontrollierte Nachuntersuchung ehemaliger Eliteathleten

Abstract: To study the potential influence of long-term, high-intensity physical training on premature osteoarthrosis of the ankle joint, we re-examined former members of the Swiss National team from 1973 in retrospective cohort study in 1988. Twenty-seven track and field long-distance runners and orienteers (mean age 42 [95% confidence interval 41-43] years), 9 bobsledders (42 [39-46] years) and a control group of 23 healthy normal men (35 [33-36] years) were investigated. Physiological and exercise characteristics of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
2

Year Published

1999
1999
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 0 publications
0
7
0
2
Order By: Relevance
“…Sample sizes were frequently small: nine studies had ≤50 participants [ 10 , 16 21 , 23 , 28 ], three studies had 51–100 [ 22 , 24 , 29 ] and six studies had >100 [ 11 , 15 , 25 27 , 30 ]. The study populations were frequently specific sub-groups within a community setting rather than representing true general populations ( Table 1 ).…”
Section: Results: Systematic Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Sample sizes were frequently small: nine studies had ≤50 participants [ 10 , 16 21 , 23 , 28 ], three studies had 51–100 [ 22 , 24 , 29 ] and six studies had >100 [ 11 , 15 , 25 27 , 30 ]. The study populations were frequently specific sub-groups within a community setting rather than representing true general populations ( Table 1 ).…”
Section: Results: Systematic Reviewmentioning
confidence: 99%
“…Fifteen studies used select sporting populations [ 10 , 11 , 15 – 26 , 30 ], one used a population with hereditary haemochromatosis [ 27 ], one utilised human cadavers [ 28 ] and one involved a small urban population in Nigeria who were attending a primary care facility with joint symptoms [ 29 ]. All studies included adults although these were frequently younger adults: in two studies age range was not reported but mean age was 35 years [ 18 ] and 50 years [ 30 ], six studies reported age range with an upper limit of 55 years [ 11 , 15 , 19 , 21 , 24 , 26 ], ten studies showed an age range which extended past 55 years [ 10 , 16 , 17 , 20 , 22 , 23 , 25 , 27 29 ]. Nine studies examined exclusively male populations [ 10 , 15 18 , 21 , 22 , 26 , 30 ] and one study examined an exclusively female population [ 20 ].…”
Section: Results: Systematic Reviewmentioning
confidence: 99%
“…The control group consisted of 19 healthy, untrained men (34.8 f 6 years, height 176.0 + 3 cm. weight 74.7 f 5 kg) who had volunteered earlier for a randomised training study and had been reexamined in 1988 [13]. Control subjects underwent the same radiological examination as the elite athletes.…”
Section: Methodsmentioning
confidence: 99%
“…Zur chronischen Instabilität des oberen Sprunggelenks liegen jedoch nur sehr wenige Daten vor. Im Orientierungslauf wird in einer Studie von Knobloch et al diese mit 60 % angegeben [9], was signifikant höher lag als die verglichenen Leichtathleten und Bobsportler. Leumann et al [10] lagen mit 73 % chronischer Sprunggelenksinstabilität im Orientierungslauf noch höher.…”
Section: Epidemiologieunclassified